USM VC: OPTIMISE RESOURCES TO ENSURE APEX 2020 SUCCESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
NIBONG TEBAL, 31 January 2016 – Universiti Sains Malaysia (USM) plans to optimise the use of available resources, including in the various engineering fields, as part of the effort to transform the university in achieving APEX 2020.